2010
DOI: 10.1017/s1751731109991625
|View full text |Cite
|
Sign up to set email alerts
|

Parent-of-origin effects cause genetic variation in pig performance traits

Abstract: In order to assess the relative importance of genomic imprinting for the genetic variation of traits economically relevant for pork production, a data set containing 21 209 records from Large White pigs was analysed. A total of 33 traits for growth, carcass composition and meat quality were investigated. All traits were recorded between 1997 and 2006 at a test station in Switzerland and the pedigree included 15 747 ancestors. A model with two genetic effects for each animal was applied: the first corresponds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 28 publications
5
65
0
Order By: Relevance
“…In general, the reliability of genetic estimates depends mainly on the availability of data such as individual records and kinship information (Mrode, 2014). The amount of kinship information depends mainly on the number of progeny.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the reliability of genetic estimates depends mainly on the availability of data such as individual records and kinship information (Mrode, 2014). The amount of kinship information depends mainly on the number of progeny.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of an advanced intercross in mice has shown that body weight is controlled in a parent-of-origin-specific manner throughout life and that about half of the variance at imprinted quantitative trait loci (iQTLs) is attributable to these effects (Wolf et al., 2008). Similarly, large pedigrees of farm animals have been used to demonstrate significant maternal and paternal influences on growth (e.g., Neugebauer et al., 2010), although in the absence of genotype data.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from genetic factors that follow Mendelian rules of inheritance, prenatal muscle development and postnatal muscle phenotype may be affected by genetic and epigenetic factors with Non-Mendelian modes of inheritance. This includes effects of mitochondrial genome [22], X- and Y-chromosomes [23], [24], non-random X-inactivation [25], microRNA (miRNA) interference [26] and genomic imprinting [24], [27][29]. Genomic imprinting, i.e., parent-of-origin dependent allele-specific gene expression [30], has been described for genes with pivotal roles in myogenesis, including IGF2 and its receptor IGF2R [31], [32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ovine Carwell locus, which exerts paternal effects on weight of M. longissimus dorsi and a shift from type IIA to type IIX myofibres, was mapped to the same chromosome region as the CLPG mutation [41][43]. More recently, statistical modelling revealed significant parent-of-origin effects attributed to genomic imprinting on postnatal absolute and relative weights of specific muscles in porcine [27] and bovine [28].…”
Section: Introductionmentioning
confidence: 99%